Pengaruh Citra Jurusan dan Kurikulum terhadap Keputusan Mahasiswa Memilih Jurusan: Analisis Multiple Regression Analysis (MRA) - Annisa Dewi Akbari; Nayla Nur Fitria; Indah Aprilia Maulidah; Eugen Valman Azis; Alifta Agdiana Dewati; Jeanice Aurellia Basri; Andi Fadli Adrian (UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG, 2026)
This study aims to analyze the factors that influence students' decisions in choosing a major in the context of competitive new student admissions, especially in private universities. The study uses a quantitative approach with a survey method through a questionnaire collected online from 201 respondents with a purposive sampling technique. Eleven independent variables were tested, including department accreditation, department reputation, department image, lecturer quality, curriculum, alumni, campus/department facilities, variety of UKM, campus partners, campus location, and job prospects using Multiple Regression Analysis (MRA). The results show a simultaneous significant model (F=12.55; p<0.001) with a coefficient of determination (R²) of 0.421 and an Adjusted R² of 0.387, indicating that 42.1% of the variation in major selection decisions can be explained by the variables in the model. Partially, the variables of department image (β=0.2235; p=0.028) and curriculum (β=0.1992; p=0.047) had a positive and significant influence on students' decisions in choosing a department, while the other variables did not show a significant influence. This finding indicates that strengthening a positive department image and presenting a relevant curriculum are strategic priorities to increase the attractiveness of a department